Experimental Air Warming of a Stylosanthes capitata, Vogel Dominated Tropical Pasture Affects Soil Respiration and Nitrogen Dynamics - Gonzalez-Meler, Miquel A.; Silva, Lais B. C.; Dias-De-Oliveira, Eduardo; Flower, Charles E.; Martinez, Carlos A. (Frontiers in Plant Science, 2017)
Background, Aims and Methods: Information on the effects of increases in air temperature on tropical systems is lacking. We investigated the effects of a 2 °C temperature increase over ambient air for 30 days on an established tropical pasture (in Ribeirão Preto, São Paulo, Brazil) dominated by the legume Stylosanthes capitata Vogel, using a T-FACE (temperature free-air controlled enhancement) system. Results: Experimental warming moderately increased soil respiration rates particularly at dusk when compared to ambient temperature. Soil respiration was positively correlated with soil temperature and moisture at mid-day but not at dusk. Soil microbial enzymatic activity decreased in response to the air warming treatment, suggesting a slower decomposition of organic matter under the elevated air temperature conditions. Foliar δ13C were not different between control and elevated temperature treatments; plants grown at the warmed plots did not show signs of water stress. The sharp decrease seen in the 15N isotopic composition of leaves from plants grown at the elevated temperature suggest increased soil N leaching and perhaps a higher proportion of N-fixation contributing to tissue N in warmed plants when compared to ambient temperature ones. Conclusion: Decreased soil enzyme capacity and increases in plant biomass in plots exposed to high temperature suggest that increased root activity may have caused the increase seen in soil respiration in this tropical pasture. This response along with rapid changes in soil and plant 15N may differ from what has been shown in temperate grasslands.